Conceptualizing Special Educational Needs Using a Biopsychosocial Model in England: The Prospects and Challenges of Using the International Classification of Functioning Framework - Norwich, Brahm (Frontiers in Education, 2016)
This conceptual paper examines the issues in the use of term ‘special educational needs’ (SEN) in England over the last 40 years and from this identifies what kind of additional needs principles are required for educational services. The paper then examines to what extent the child and youth version of the International Classification of Functioning, Disability and Health (ICF-CY) has the potential to meet these assessment principles. The paper illustrates that the potential of the ICF-CY by reference to studies that show how the ICF has been used to enhance assessment relevant to programme planning. Several studies showed how assessment instruments designed for diagnostic assessment could be linked to ICF dimensions. Other projects illustrated how the ICF framework can also provide the basis for designing dependable measurement questionnaires. But, measurement issues still need to be addressed by further development research. There has been relatively little use of the ICF-CY in educational settings and for eligibility decisions about scarce education provision, despite the ICF’s use in Portugal and parts of Italy and Switzerland. Research in these countries show the usefulness of the ICF as a resource for decision-making, but analyses of Individual Educational Programmes (IEPs) show fidelity issues in the ICF use and the need for enhanced teacher training. The Swiss conceptual expansion of the ICF-CY takes account of an educational perspective and its implementation with procedures and materials has direct relevance to England. The Swiss development brings out the importance of understanding the different aspects of the ICF and how it can be adapted for different purposes. In adopting the ICF for an additional needs framework in education, eligibility decisions will require norms about functioning and the environment. It is concluded that these norms should be negotiated with service users who are to be treated as having rights to participate in assessment and decision-making. It is concluded that there is potential for the development and use of an ICF informed approach to assessment and decision-making in England.